2022
DOI: 10.3389/fimmu.2021.811351
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of CSF GFAP, CCN5, and vWF Levels Enhances the Diagnostic Accuracy of Clinically Defined MS From Non-MS Patients With CSF Oligoclonal Bands

Abstract: BackgroundInclusion of cerebrospinal fluid (CSF) oligoclonal IgG bands (OCGB) in the revised McDonald criteria increases the sensitivity of diagnosis when dissemination in time (DIT) cannot be proven. While OCGB negative patients are unlikely to develop clinically definite (CD) MS, OCGB positivity may lead to an erroneous diagnosis in conditions that present similarly, such as neuromyelitis optica spectrum disorders (NMOSD) or neurosarcoidosis.ObjectiveTo identify specific, OCGB-complementary, biomarkers to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
(34 reference statements)
2
4
0
Order By: Relevance
“…Astrocytes at the edge of MS chronic active lesions as well as in the glia limitans and ependyma show high expression of GFAP and may reflect sources of increased levels associated with smoldering injury in the context of focal lesions, as well as in the subpial cortex and periventricular regions, respectively. Elevated CSF GFAP has also been reported in early MS, supporting its potential utility across the disease continuum . We identified only a moderate correlation between serum and CSF GFAP levels and did not detect an association between serum GFAP levels and progressive disease outcomes (consistent with other similarly sized studies).…”
Section: Discussionsupporting
confidence: 85%
“…Astrocytes at the edge of MS chronic active lesions as well as in the glia limitans and ependyma show high expression of GFAP and may reflect sources of increased levels associated with smoldering injury in the context of focal lesions, as well as in the subpial cortex and periventricular regions, respectively. Elevated CSF GFAP has also been reported in early MS, supporting its potential utility across the disease continuum . We identified only a moderate correlation between serum and CSF GFAP levels and did not detect an association between serum GFAP levels and progressive disease outcomes (consistent with other similarly sized studies).…”
Section: Discussionsupporting
confidence: 85%
“…CCN5 measurement increased both by 5%, while measurement of GFAP increased the specificity to 100% [154]. According to them, combining CCN5, vWF, GFAP with OGP is able to accurately discriminate between OGP positive MS and other neurological conditions with OGP positivity [154].…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 93%
“…In a very recent, high quality evaluation, Probert et al investigated different CNS biomarkers that can help distinguish MS from non-MS controls as compared to OGP positivity. They found that the measurement of connective tissue growth factor/cysteine-rich protein/nephroblastoma overexpressed-5 (CCN5), von Willebrand factor (vWF) and glial fibrillary acidic protein (GFAP) increased the specificity and sensitivity level of the diagnosis as compared to solely identifying OGP [154]. CCN5 measurement increased both by 5%, while measurement of GFAP increased the specificity to 100% [154].…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations